Representation Analysis of Verbal Sexual Violence in “Trust” Movie - Kharisma Yulia Mahayani, Ni Ketut; Juniartha, I Wayan (Humanis, 2025)
Sexual violence against children and adolescents is a critical issue that demands urgent public and academic attention, particularly in how such violence is represented and interpreted in media. This study aims to concrete the meaning of scenes of sexual violence representation in verbal and visual sign. Trust is notable for its bold and explicit portrayal of sexual violence, making it a relevant text for examining audience reception. The objective of this research is to describe the meaning in such scenes, especially those involving child and adolescent victims. Using Stuart Hall’s encoding/decoding model as the theoretical framework and Barthes’s meaning theory, this study employs a qualitative descriptive method, analyzing textual elements through initial-viewing and analysis. The findings show that verbal sexual violence in Trust portrayed through Charlie’s expressions and gestures. This study emphasizing how the multifaceted impact of sexual violence on victims, highlighting both psychological and physiological consequences. Moreover, this study offers insight on the audience’s role as active interpreters of media texts involving sensitive social issues.